Tuberculosis in the family context: an experience report (Research, Society and Development, 2022)
The present study aims to describe the experience of a family member in the follow-up of a patient deprived of liberty infected with tuberculosis, highlighting the weaknesses of the care provided. This is an experience report with a descriptive qualitative approach, which contributes to the writing of experiences and knowledge of various themes, being recognized in the importance of discussing. It refers to the experience of a nursing student in the 3rd semester in the follow-up of a patient deprived of liberty. The experience occurred during the need for care of the family patient, who remained in a penitentiary for approximately three years that the patient was not diagnosed with tuberculosis and, two years after his departure, the bacteria manifested in his body. The assistance of a multiprofessional team for patients with tuberculosis has the role of giving the necessary guidelines to avoid the contagion and spread of the pathology, being necessary the necessary guidelines on active tuberculosis, in which professionals and sectors work the patient's clinic and give him/her appropriate assistance.